Validation and attempts of revision of the MDS-recommended tests for the screening of Parkinson's disease dementia - Isella, V.; Mapelli, C.; Siri, C.; De Gaspari, D.; Pezzoli, G.; Antonini, A.; Poletti, M.; Bonuccelli, U.; Vista, M.; Appollonio, I.M. (Parkinsonism & related disorders, 2014)
The Movement Disorders Society (MDS) formulated diagnostic criteria and assessment guidelines for the screening of dementia in Parkinson's disease (PD). We carried out a validation of the cognitive measures suggested in the screening algorithm (i.e. the Mini Mental State Examination – MMSE – total score, serial 7s subtraction, 3-word recall, pentagons copy, and one minute letter fluency) in 86 patients with PD. Thirty-six percent of participants were diagnosed with dementia using the MDS algorithm, but with the Dementia Rating Scale instead of the MMSE. The original MDS procedure misclassified 11 patients (12.8%) as false negatives and 3 (3.5%) as false positives, leading to 65% sensitivity and 95% specificity. The main reason for misdiagnoses was insensitivity of the MMSE total score. Three attempts were made to reach a better screening performance, which warrants high sensitivity more than high specificity: 1. exclusion of the MMSE total score as a diagnostic requirement; 2. determination of a better cut off through Receiver Operating Characteristic curve analysis; 3. replacement of the MMSE with the equally undemanding, but more PD-specific, Mini Mental Parkinson. The first two strategies generally yielded high sensitivity, but poor specificity. The best outcome was achieved using a Mini Mental Parkinson total score <27 as cognitive criterion: sensitivity was 87% and negative predictive value was 90%; however, specificity was only 67%. Our findings seem to suggest that MDS practical guidelines are specific, but might benefit from the use of more PD-oriented tools than the MMSE in terms of sensitivity.